Safety of home parenteral nutrition during pregnancy. Issue 1 (February 2017) - Theilla, Miriam; Ławiński, Michał; Cohen, Jonathan; Hadar, Eran; Kagan, Ilya; Perkewick, Marek; Singer, Pierre
Summary: Background & aims: Few studies have examined the effect of total parenteral nutrition which is lipid-based given throughout pregnancy to patients unable to obtain adequate nutrition by the oral route. In this study we examined the use of lipid-based home parenteral nutrition (HPN) in 7 pregnant women, commenced either before or during pregnancy, and their intra-pregnant course as well as a 2-year follow-up of their offspring is described. Methods: HPN was formulated on an individual basis and protein administered in a dose of 0.8–1.1 g/kg during the three trimesters. Lipid emulsions included long chain triglycerides or olive-oil based formulae and all patients received trace elements. Data were collected during the course of pregnancy and at birth while infants were followed for a period of between 6 months and 2 years using medical records and questionnaires. Results: In total, we studied 9 pregnancies (in 7 women). HPN was administered for a median of 9 months (range 3–9 months). The mean energy provided during the 1st, 2nd and 3rd trimester was 9297 ± 2797 kcal/week, 9148 ± 2629 kcal/week and 8564 ± 4059 kcal/week resp. The mean increase in weight during the pregnancy was 9 ± 5 Kg. The only complications noted during the pregnancy consisted of 3 episodes of catheter-related infections which were successfully treated by antibiotics. The infants were born after a mean of 38.00 ± 1.55 weeks of gestation, with a mean first minute Apgar score of 8.7 ± 1.8 which increased to 9.8 ± 0.4 after 10 min. The mean infant birth weight was 2.45 ± 0.37 kg. No complications were noted at birth apart from one infant who suffered from torticollis which resolved spontaneously. During follow up, a decrease in hemoglobin related to low iron levels was noted in 1 infant, 2 infants were noted to be allergic to pollen and one underwent a scrotal hernia reduction. No developmental problems have been observed, neither physiological nor psychomotor, over the 2-year follow-up period. Conclusions: The authors suggest, based on, the current study, that lipid-based HPN for pregnant women is a safe method for meeting the nutritional demands of both mother and fetus, and may be administered throughout the pregnancy.